1996
DOI: 10.1007/bf00020614
|View full text |Cite
|
Sign up to set email alerts
|

The pea early nodulin gene PsENOD7 maps in the region of linkage group I containing sym2 and leghaemoglobin

Abstract: The early nodulin gene, PsENOD7, is expressed in pea root nodules induced by Rhizobium leguminosarum bv. viciae, but not in other plant organs. In situ hybridization showed that this gene is transcribed during nodule maturation in the infected cells of the proximal part of the prefixation zone II. At the transition of zone II into interzone II-III, the level of PsENOD7 mRNA drops markedly. PsENOD7 has no significant homology to other genes. RFLP mapping studies have shown that PsENOD7 is located in linkage gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Subsequently Kozik (1996) concluded that sym19 must be linked to ENOD40, about 17 cM from sym2 on linkage group I.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently Kozik (1996) concluded that sym19 must be linked to ENOD40, about 17 cM from sym2 on linkage group I.…”
Section: Resultsmentioning
confidence: 99%
“…While numerous bacterial genes have been identi®ed, there has been limited progress in identi®cation of plant genes that have a de®ned role in nodule development. As a ®rst step towards identifying such genes, numerous plant mutants defective in nodulation (Sagan et al 1994, Kozik 1996 and references therein) have been isolated. One such pea mutant, line P55, is defective for the rhizobial and endomycorrhizial symbioses (Duc and Messager 1989;Sagan et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Expression of the early nodulin gene ENOD40 is localized in pericycle zone of root and can be induced by exogenous application of Nod factors (for review see Pawlowski and Bisseling, 1996). In P. sativum nodules, ENOD7 gene is expressed in the proximal part of the prefixation zone II (Kozik et al, 1996). In legume nodules, ENOD2, MtPRP and nodule-specific lectin gene are expressed in parenchyma and these products provide an O 2 diffusion barrier in order to preserve nitrogenase activity (for review see Pawlowski, 1997).…”
Section: Biology Of Nodules and Mycorrhizamentioning
confidence: 99%
“…Linkage group I of pea is the genomic region with the highest density of legume genes involved in the symbiosis with Rhizobium leguminosarum bv viciae, containing several symbiotic genes within a 20-cM interval (Weeden et al 1990;Temnykh et al 1995a, b;Kozik et al 1996;Schneider et al 1999). One of these genes is SYM2 that was first identified in the pea accession 'Afghanistan' where it controls infection by rhizobia in a Nod factor structure-dependent manner (Firmin et al 1993;Geurts et al 1997).…”
Section: Introductionmentioning
confidence: 99%